Prescribing pattern of drugs in alcohol dependence in a tertiary care hospital - Dube, Upasana; H., Shwetha; P., Shanmukananda; R., Veena D.; Kumar, Ashok (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Alcohol dependence is one of the more serious public health issues in the world. It not only affects health but is also a social and economic burden. Pharmacotherapy is the main stay of treatment along with behavioural therapy for alcohol addiction. The present study was done to analyse the prescribing pattern of drugs used in alcohol dependence. Methods: The present study is a retrospective study which was carried out in the Department of Psychiatry, Dr. B.R. Ambedkar Medical College, Bengaluru from March 2016 to August 2016. Demographic, disease and treatment details were collected and entered in the case proformas. The results were analyzed using descriptive statistics. Results: A total of 125 prescriptions were analyzed. The most common age group was between 30-60 years with a male predominance (95.2%). 72% of patients were treated for alcohol dependence whereas 28% who had other co morbidities like psychosis and depression were treated appropriately. The most commonly prescribed drugs were Vitamins (74.4%), Benzodiazepines (BZDs) (56.8%), anti-craving drugs (52%), antipsychotics (20%) and anti-depressant drugs (8%). Lorazepam (45.6%) and Baclofen (46.1%) were the most common drugs prescribed among BZDs and Anti-craving drugs respectively. For affective disorders Olanzapine (36%) was the commonest drug prescribed. Conclusions: This study reveals that alcohol dependence is accompanied by other co-morbidities like psychosis, depression and anxiety. Combined therapy of Vitamins, BZDs, Anti-craving drugs along with Antipsychotic or Antidepressant drugs have been prescribed to the patients. Newer anti-craving drugs like Baclofen, Acamprosate and Naltrexone have also been prescribed.